The use of mustard seed oil meal as a protein supplement for fattening pigs in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
Protein supplements are essential to profitable pork production whether it be the maintenance of the breeding herd, growing the pigs, or fattening pigs for market. Previous tests at this station have shown the advantage and profit in feeding tankage and other protein supplements with corn or other grains when pigs are fed in the dry lot or on pasture. About a year ago the Department of Animal Husbandry was asked to conduct some experimental feeding tests with mustard seed oil meal. This meal was being produced in a Kansas seed oil extraction plant by expressing the oil from wild mustard seed. The seed had been shipped from northern wheat growing areas, where it had been separated from Spring wheat, which it contaminated very badly. There was a considerable potential supply of this seed and the meal or residue remaining from the oil extraction contained considerable protein, so it was thought that it might have considerable value as a protein supplement for livestock. Consequently the Department of Animal Husbandry became interested and carried on some feeding experiments.
Keywords: Swine; Mustard seed oil meal; Protein; Dry lot